Contribuição ao projeto e dimensionamento da superestrutura de pontes rodoviárias em vigas mistas de aço e concreto - Souza, Victor José Luiz de (2012)
Even the metal bridges known for overcoming large spans, designed and implemented by large offices, this paper wishes to present concepts that can be applied in practical design of Steel-Concrete composite bridges of short and medium span, because those are the most common in national highways, and there is also a lack of professionals to design them into steel in Brazil. In the few studies dedicated to this subject, there is no specific normalization in steel bridges, and there is a lack of bridges on local roads throughout the country. The steel bridge or the Steel- Concrete composite bridges provides a construction that is both quick and of easy recovery. At first it discusses the main structural systems, features and behaviors of composite steel bridges and concrete. It also describes the analysis procedures to actions on bridges according to the U.S. standards (AASHTO:2002 & 2005), European (EC-1:1991) and Brazilian (NBR 7188:1984). It is also an objective of this study to understand the design philosophy of AASHTO:2002, regarding the definition of actions, analysis models, ensuring the joint behavior of steel beam and concrete deck, ultimate limit states and of service and resistance of the mixed system deck, verifying the possibilities / needs of adaptation to the national reality, standard frequently used by Brazilian designers. This study aims to enrich the national literature regarding to Steel-Concrete composite bridges and according to comparisons made to the design and scaling guide, set rules for a calculated script for these mixed systems, bridges, viewing adjustments for the development of those directed to Brazilian realities.